Smart electroconductive bioactive ceramics to promote in situ electrostimulation of bone. Issue 9 (7th March 2015) - Mata, Diogo; Oliveira, Filipe J.; Neto, Miguel A.; Belmonte, Manuel; Bastos, Alexandre C.; Lopes, Maria A.; Gomes, Pedro S.; Fernandes, Maria H.; Silva, Rui F.
<x xml:space="preserve">Abstract</x> Cell functions were controlled in situ by an efficient mechanism of delivering electrical stimuli involving conductive biomaterials and non-invasive techniques.